An Evaluation of the Role of Environmental, Social and Economic Factors in Architects' Choice of Building Materials - Evci, Melek Melodi; Ciravoglu, Aysen (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2015)
The environment is in an ever-changing state as a result of humankind's ongoing relationship with nature. Recent developments in industry and technology are resulting in a diminishment of the benefits of environmental change for all forms of life, and the lack of awareness in the construction sector of the necessity for sustainable approaches is leading to an ever more rapid depletion of natural resources. A combination of these factors has now led to damage of the natural balance and triggered the global warming that is threatening our world. One response to this in recent years has been the development of numerous building and material assessment models that aim to evaluate the environmental impact of buildings and materials. While each model evaluates building materials using different methods, all share one characteristic, in that they mainly deal only with the environmental effect of building materials. Hence, while research into the economic, social and cultural factors involved in building material choices is of equal importance, study numbers are very limited in this area. This article aimed to make a survey the deficiencies of current models, and evaluate architects' sensitivity in choosing materials. In this context, a survey study was conducted to compare and evaluate the criteria architects use when selecting materials.
Keywords: Building assessment models; sustainability; building material choice; Architecture